ANALISIS KONTRIBUSI LABA PENJUALAN CAT JOTUN PADA TOKO WARNA-WARNI DI SAMARINDA - nirmalasari, gita govinda (EKONOMIA, 2013)
GITA GOVINDA NIRMALASARI, Every company has a goal to run activities for the sustainability of the business makes a profit. In order to achieve maximum profit, then the firm must consider two important factors, namely, the amount of profitable sales and expenses are sacrificed to achieve these sales. Problem of this study was to determine among Jotun Paints Brand Liquid 2.5 Litre, 5 Litre Brand Paints and Jotun Oil 1 Liter and 5 Liter which contributed most of the profits for the Colorful Shops in Samarinda.The hypothesis of this study is